Leadership and Management in Undergraduate Medical Education - Nicolaou, Cornelia; Nicolaou, Nicoletta; Nicolaou, Persoulla; Nicolaides, Paola; Papageorgiou, Alexia (Global journal of Business and Integral Security, 2026)
Leadership and management competencies are essential for effective medical practice, yet are not systematically taught in medical undergraduate training. This pilot study assesses the opinions of medical students and healthcare professionals on the relevance of, and self-reported competence in, 22 leadership and management skills, to inform the development of a curricular module. Participants completed a structured questionnaire. Descriptive and inferential statistics were used to summarize and compare groups. Overall, both groups rated most skills as highly relevant, with Communication receiving unanimous importance. Professionals rated Ethics significantly higher than students (p = 0.024), with trends toward higher ratings in Creativity and Inspiring Others. Across nearly all skills, competence ratings lagged behind relevance, with the largest gaps in technical and administrative domains. These findings highlight the need to introduce structured leadership and management training early in the medical curriculum, incorporating experiential and practice-oriented learning to prepare future physicians for complex healthcare roles.